Photoinduced Reaction of Excited Triplet 9,10-Anthraquinone Quenched by Antioxidant Vitamin C (Journal of Atomic and Molecular Sciences, 2014)
The quenching of the photoinduced excited triplet of 9,10-anthraquinone $(^3AQ^*)$ by Vitamin C (VC) has been studied in ethylene glycol-water $(EG-H_2O, EG/H_2O=9/1, v/v)$ homogeneous by using time-resolved electronic paramagnetic resonance(TR-EPR) and laser flash photolysis techniques. According to the chemicallyinduced dynamic electron polarization (CIDEP) and transient absorptive spectra, thereaction intermediates and the reaction mechanism have been analyzed. The rate constantfor the quenching of excited triplet $^3AQ^*$ by VC has been measured. The resultsindicate that $^3AQ^*$ can capture hydrogen atom not only from ethylene glycol moleculebut also from VC. The strong CIDEP signal of VC monoanion radical indicates that thequenching of VC to $^3AQ^*$ is obvious. The rate for the quenching of $^3AQ^*$ by VC isnearly diffusion-controlled.
Keywords: 9; 10-anthraquinone; Vitamin C; time-resolved electron paramagnetic resonance (TREPR); transient absorptive spectrum; chemically induced dynamic electron polarization (CIDEP).